Clinical efficacy and preventive role of the pre-participation physical examination in Italy - Di Luigi, L.; Pelliccia, A.; Bonetti, A.; Francavilla, G.; Ganzit, G. P.; Veicsteinas, A.; Accettatura, D.; Bagnini, A.; Cantore, R.; Castagna, W.; Ciaciarelli, C.; Costini, G.; et al. (Österreichisches Journal für Sportmedizin, 2005)
The medical supervision of athletes is a primary task of the sports medicine; a basic tool to accomplish this is the pre-participation physical examination (PPE). The purpose of the PPE as conducted in Italy in Order to give specific sports eligibility (VIMeS, Visita di Idoneità Medico Sportiva) is not to disqualify unfit individuals from practicing sports, but rather to ensure that subjects predisposed to or affected by a disease can practice sports safely. In the present study we evaluated factors predisposing to disease and determined which diseases, while not necessarily inducing to non-eligibility for sports activities, may be revealed by the VIMeS. Variables included medical history, anthropometric and functional characteristics (height, weight, body mass index, heart rate, blood pressure). A total of 32 652 athletes (80% males, 20% females) underwent a physical examination and diagnostic procedures (ECG, spirometry, urine tests, etc.) according to the Italian PPE (VIMeS) protocol at the 19 Sport Medicine Operative Units associated with the Italian Federation of Sports Medicine (FMSI). The results showed that the VIMeS, as conducted according to the compulsory protocol (including examination by a sports medicine specialist, ECG, spirometry, etc.), was able to detect a not insignificant percentage of subjects unfit for sports (1.3%) and, more importantly, in highlighting: A) the presence of many risk factors such as smoking (0.8% of subjects 11-15 years old and 27.4% of those 26-30 years old) and alcohol consumption (11.7%); B) the presence of positive family history for diseases (endocrine-metabolic disorders [61.8%], vascular disorders [16.7%], cardiac disorders [12.8%]; C) a relevant proportion of disorders diagnosed at the VIMeS (20.8%). This subjects were subsequently referred to appropriate therapy and/or monitoring programs. Taken together, this study shows that the VIMeS is an effective filter for health care, epidemiology and prevention).